A new genus with one new species of Phaloriinae from western Yunnan, China (Orthoptera: Phalangopsidae: Phaloriinae) - Chen, Guang-Yu; Xu, Yue; Liao, Wang; He, Zhu-Qing (Zootaxa, 2019)
One new genus, Neophaloria He gen. nov., is established with one new species, Neophaloria dianxiensis He sp. nov., from western Yunnan, China. The characters of this new genus are: long and widened rachis and the epiphallic lobes and ectoparameres curved inwards. COI genes and songs are provided. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).